Effects of the Adsorption of Ba Ions on the Electrical Double Layer at the 4th Group Metal Oxide/Electrolyte Interface - W. Janusz; A. Gałgan; E. Skwarek (Adsorption Science & Technology)
The specific adsorption of Ba 2+ ions onto titanium dioxide (rutile and anatase structures), zirconium and hafnium dioxide was investigated as a function of the concentrations of Ba 2+ ions and NaCl and the pH by a radioisotopic method. The initial Ba 2+ ion concentration ranged from 5 × 10 −6 mol/dm 3 to 0.001 mol/dm 3 while the pH was changed over the range 3–10. The NaCl solution used as a background electrolyte was employed at concentrations of 0.1, 0.01 and 0.001 mol/dm 3 , respectively. The adsorption measurements were complemented by potentiometric titrations of the titanium dioxide suspensions (to determine the surface charge) and electrophoretic measurements. The apparent reaction constants of the surface hydroxyl group with Ba 2+ ions were calculated numerically from the Ba 2+ ion adsorption data.